“Life Would Never Feel This Good Again”: The Use of Pastiche in Edgar Wright’s The World’s End (2013) - Diana Ortega Martin (Anglica. An International Journal of English Studies)
This article explores the ways in which pastiche, the past, and national iden- tity are portrayed and navigated in the concluding film of Edgar Wright’s The Cornetto Trilogy: The World’s End (2013). By focusing on the relationship between the use of the past and pastiche, it will be considered how they are employed to negotiate the notion of national identity. Through its comedic strategies and tropes, the film rebels against a homogenised version of Englishness based on mythical assumptions of the past and striving toward perfection. The dissection of the cinematic structure of pastiche will reveal a temporal framework questioning contemporary narratives of national identity. Moreover, the exploration of nostalgia and the past as places of retreat, as well as pastiche as a device of comedic criticism, enable Wright to offer a portrait of Englishness as struggling to recover its identity amidst a turbulent and apocalyptic time.